BIOMAT 2012 : International symposium on mathematical and computational biology, Tempe, Arizona, USA, 6-10 November 2012 - Mondaini, Rubem P. (World Scientific, 2013)
This is a book of a series on interdisciplinary topics of the Biological and Mathematical Sciences. The chapters correspond to selected papers on special research themes, which were presented at BIOMAT 2012 International Symposium on Mathematical and Computational Biology, in Tempe, Arizona, USA, November 6-10. This book contains state-of-the art articles on special research topics on mathematical biology, biological physics and mathematical modeling of biosystems; comprehensive reviews on interdisciplinary areas written by prominent leaders of scientific research groups. The treatment is both pedagogical and advanced in order to motivate research students as well as to fulfill the requirements of professional practitioners.